ESL Teachers' Computer Self-Efficacy, Attitudes Toward Computer and Classroom Computer Use. - Hong, K. S.; Chai, M. L.; Tan, K. W.; Hasbee, U.; Ting, L. N. (Pertanika Journal of Social Sciences & Humanities, 2014)
Although computers play a vital role in the field of education, teachers remain as one of the key determinants of the success of any technology innovation and initiative in education. Specifically, teachers' computer self-efficacy and attitudes towards computers are posited as having an influence on computer use for classroom teaching. A survey method is used in this study to determine ESL or English as a Second Language teachers' level of computer self-efficacy, attitudes towards computers and classroom computer use, in addition to investigating gender differences and relationships between the three variables. A questionnaire is administered to 102 ESL teachers in ten urban secondary schools in Kuching, Sarawak, Malaysia. The findings of this study show that the ESL teachers have moderate level of computer self-efficacy, attitudes towards computer use and computer use in the English classroom. Male teachers have a significantly higher computer self-efficacy than the female. In terms of teachers' attitudes towards computers and computer use, there is no significant difference among teachers of different genders. There is a significant low positive relationship between teachers' self-efficacy and teachers' attitudes towards classroom computers. It indicates that if the teachers' computer self-efficacy increases, their attitudes towards classroom computers will also increase. The results indicate that there is a low but positive significant relationship between teachers' computer self-efficacy and their computer use in Malaysian classrooms. Thus, if the teachers' computer self-efficacy increases, their use of classroom computers will also increase. However, there is no relationship between teachers' attitudes towards computers and actual classroom computer use. The findings of the study indicate that computer self-efficacy of ESL teachers is an important factor to consider in enhancing their attitudes towards computers and computer use in the classroom.